THE ROLE AND IMPORTANCE OF METHODOLOGICAL SCIENCE IN THE TRAINING OF FUTURE MUSIC TEACHERS (BASED ON FOREIGN AND NATIONAL EXPERIENCE) (American Journal of Interdisciplinary Research and Development, 2026)
In my article mainly future music their teachers preparation in the process methodology science place and importance foreign and national experiments based on analysis In the study methodology science professional competence in formation role, reflexive and innovative approaches, national music legacy with integration scientific and pedagogical point from the point of view illuminated. Also, music teacher 's methodical thinking, creative approach, pedagogical skill and creative competence in development methodical of sciences caught place open given. Foreign education institutions experience and Uzbekistan supreme education in the system methodical preparation processes comparative analysis made, they harmonization through music education efficiency increase possibility Based on. Research as a result methodology science future music teacher's professional in formation main mechanism that conclusion made.